PERENCANAAN PAJAK PADA HOTEL WISATA INDAH - Agung Nurmansyah (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2016)
In the hotel competition intensifies, it takes strategy to reduce costs or increase revenue. One of the things that can be achieved is a tax cost savings. Tax savings or tax planning are important steps to do menurunan tax costs that should be paid to countries without violating tax laws. Steps to be done is to analyze the company’s revenue and cost analysis of the company. But before it must be analyzed whether the company has implemented tax planning or not. For a case study of Wisata Indah hotel not carry out tax planning.